ANTIMICROBIAL ACTIVITES OF COW DUNG EXTRACTS AGAINST HUMAN PATHOGENS - Rajeswari, S.; Poongothai, E.; Hemalatha, N. (International Journal of Current Pharmaceutical Research, 2016)
Objective: For control of microbial infections and diseases, various synthetic drugs and chemical formulations are currently in use. But due to the problem of microbial drug resistance, new alternative synthetic drugs have been explored. Similarly, antimicrobial activities of so many natural products have also been explored. Methods: In this various study extracts of cow dung possessed antimicrobial property against human pathogens like Klebsiella pneumonia and Escherichia coli. Results: The Indian cow dung extracted possessed superior antimicrobial activity than other cow dung types and showed antimicrobial property against all the test microorganisms. Since cow dung and buffalo dung are abundant in nature, which make the process cost effective with processing ease and thus are a promising solution for a variety of health problems in the near future. Conclusion: The medicinal properties of these cow dung and buffalo dung can be exploited to formulate drugs for several diseases caused by antibiotic resistant pathogenic microorganisms.